Mothers and daughters: intergenerational patterns of reproduction - Pouta, Anneli; Järvelin, Marjo-Riitta; Hemminki, Elina; Sovio, Ulla; Hartikainen, Anna-Liisa (European Journal of Public Health, 2005)
Background : The objective of this study was to assess intergenerational mother–daughter patterns of reproduction. Methods : In 1966, 12 055 pregnant women in Northern Finland, representing 96% of all births in the region, responded to a questionnaire in mid-gestation. In 1997–98, the 31-year-old daughters born from those pregnancies were sent a questionnaire and 4523 (80%) responded. Reproduction was compared between all mother–daughter pairs ( n =4523) and separately for the pairs ( n =489) of similar age (mothers 30–32 years). Results : The menarcheal ages of the mothers and their daughters correlated slightly (Spearman correlation coefficient 0.206). The probability of the daughter to be multiparous was higher if her mother was multiparous at the time of the daughter's birth than if she was not. No association in the rate of spontaneous abortions was found. The first pregnancy of the daughters born from unwanted pregnancies was more often unwanted than the first pregnancy of the wanted daughters, after adjusting for parity ( P =0.004). The analysis of the age-matched mother–daughter pairs gave similar results. Conclusion : A positive association between mothers and daughters in menarcheal age, parity and desirability of pregnancy was found.